130 Safety, β-sarcoglycan expression and functional outcomes from systemic gene transfer of rAAVrh74.MHCK7.SGCB in LGMD2E/R4. Issue 6 (27th May 2022) - Rodino-Klapac, Louise; Pozsgai, Eric; Lewis, Sarah; Griffin, Danielle; Meadows, Aaron; Lehman, Kelly; Church, Kathleen; Lowes, Linda; Richardson, James; Mendell, Jerry
Abstract : Limb-girdle muscular dystrophy type 2E/R4 (LGMD2E/R4) is caused by β-sarcoglycan (SGCB) gene mutations, resulting in loss of functional protein and dystrophin-associated protein complex disruption. LGMD2E/R4 symptoms include hip/shoulder muscle weakness, cardiac involvement, and elevated creatine kinase (CK). Here, we report initial findings of a Phase 1/2 open-label, systemic gene transfer trial (NCT03652259 ) of rAAVrh74.MHCK7.hSGCB (SRP-9003), designed to restore functional SGCB, in patients with LGMD2E/R4. Six patients (aged 4–15 years, negative for rAAVrh74 antibodies, 100-meter timed test >40%) received a single SRP-9003 IV infusion of 1.85×1013 vg/kg (Cohort 1, n=3) or 7.41×1013 vg/kg (Cohort 2, n=3). Prednisone (1 mg/kg/day) was initiated 1 day before (30–60 days taper). Endpoints: safety (primary), SGCB expression (secondary), others: North Star Assessment of Limb-girdle Muscular Dystrophies (NSAD), timed functional tests. SRP-9003 is well tolerated with no unexpected immunologic responses observed. All patients demonstrated efficient transduction and robust SGCB expression post-infusion, with subsequent sarcoglycan complex reconstitution and CK reduction. Six months after SRP-9003 infusion, both patient cohorts experienced functional improvements. Cohort 1 had data available up to 18 months indicating NSAD and timed test improvements were maintained over time. These data suggest long-term efficacy of SRP-9003 gene-transfer therapy, supporting advancement of the clinical development program. jrichardson@sarepta.com 90